Differential Impact of Climate Change and Human Activities on Runoff Changes in the Upper Reaches of the Yellow River - LI Fang; ZENG Biao; LI Xungui; SHEN Yanqi (Renmin Zhujiang)
The impact of climate change and human activities on runoff varies with geographic location,climate background,and time scale.How to quantify their differential impacts has important practical significance.Taking the basin above Lanzhou Station of the Yellow River (YR) as the research area,this paper employs the SWAT model to study the differential impacts on and leading factors of runoff changes at different spatial and temporal scales of climate change and human activities and to explore the leading driving factors of and their contributions to runoff changes in different sections. The results show that the evaluation indexes R2 and NSE of five hydrological stations are all larger than 0.8.During the study period,the runoff changes in the source area of the YR were generally insignificant,and the runoff downstream declined earlier and more obviously than that upstream.The change in runoff in the middle section of the YR from 1986 to 2005 was affected by both climate change and human activities.After 2005,human activities were the leading factor for the reduction of runoff.The runoff changes in the lower part of the YR from 1986 to 1995 were jointly affected by climate change and human activities.The gradual strengthening of human activities was the main cause of runoff changes after 1995.The rapid development of industry,agriculture and urban agglomerations and the successive construction of hydropower stations have led to a change in the differential driving characteristics of runoff changes from “climate control” in the base period to “co-control by climate change and human activities” and finally to “dominant human activities.”